Does Freedom of Association under the Charter Include the Right to Strike after B.C. Health - Prognosis, Problems and Concerns Freedom of Association, Charter Values, and Strikes - Etherington, Brian (Canadian Labour & Employment Law Journal, 2009)
Providing his prognosis for the future of a right to strike, in light of the Supreme Court of Canada's decision in B.C. Health, the author argues that the Court will likely recognize constitutional protection for such a right. In his view, based on the scope offreedom of association set out in that decision, as well as the adoption of a "substantial interfer- ence" test, government measures will probably be held to violate s. 2(d) of the Charter if they totally remove the right to strike, or restrict it so severely as to deny access to a meaningful process of collective bargain- ing. However, turning to a consideration of the problems and concerns that would arise from Charter protection for a right to strike, the author suggests that recognition of a broad, open-ended right may open the door to challenges to the numerous restrictions on strike activity found in Canadian labour relations statutes, and embroil the courts in ongoing review of legislative choices on policy issues. Thus, he expects that the Supreme Court will recognize only a limited right to strike - one in which the legislature would be permitted to substitute strikes with some other fair impasse resolution mechanism (such as interest arbitration), in situations where there are policy reasons for withholding the right to strike or for bringing an end to a strike that threatens the public interest.